Phytochemical composition of Verbascum stachydifolium Boiss & Heldr. var. stachydifolium growing in Türkiye and in vitro analysis of wound healing activity - Kaptaner İğci, Bahar and Aytaç, Zeki (Archives of Biological Sciences, 2023)
Paper description: The aim of this study is to support alternative treatment methods that will provide wound healing and to investigate the molecular and phytochemical characteristics of Verbascum stachydifolium The scratch assay was used to assess wound healing activity in vitro, qRT-PCR and ELISA were performed to evaluate the expression of selected biomarkers, HPLC was used to determine the phytochemical components of stachydifolium. stachydifolium exhibited a wound healing potential by increasing the expression of collagen and cytokines FGF7, TGF-b1 and VEGF. The plant also possesses antioxidant activity. stachydifolium emerges as a potential source for plant-based wound healing preparations. Abstract: This study aimed to investigate the phenolic content, antioxidant activity, cytotoxicity and the in vitro wound healing activity of methanolic and aqueous extracts of Verbascum stachydifolium Boiss & Heldr. var. stachydifolium. Total phenolic and flavonoid contents and antioxidant activity were measured using spectrophotometry-based methods. Quantitative analysis of the selected phenolics was performed by HPLC. The cytotoxic effects of the extracts on L929 mouse fibroblast cells were evaluated by the MTT assay. The migration of treated fibroblast cells was assessed by the cell scratch assay. The expressions of type I collagen, FGF7, TGF-β1 and VEGF were evaluated by qRT-PCR and ELISA. The HPLC-based analysis revealed the presence of different phenolic compounds at varying amounts and high antioxidant activities were detected. The cytotoxicity assay results indicated that the methanolic and aqueous extracts did not exhibit any cytotoxic effect on fibroblast cells when used up to 500 µg/mL concentration. Fibroblast migration was stimulated to the highest degree by the aqueous extract obtained by maceration as observed in the scratch assay at 60.4% closure. The molecular mechanism of the wound healing activity involves the upregulation of the analyzed genes.